Interlocking frame window / Muhammad Nazmi Hakim Zainal and Ezzat Fahmi Ahmad - Zainal, Muhammad Nazmi Hakim; Ahmad, Ezzat Fahmi (2024)
Interlocking frame windows are a new type of frame window structure that provides a comprehensive and efficient way to handle both practical and aesthetic concerns, making them an essential option in the construction industry. This paper explores the innovative features and benefits of interlocking frame windows with a primary emphasis on their joint aspects, discussing their potential applications in the construction industry and their transformative impact on both functionality and design. This study proposes an innovative idea for the construction industry, especially for the Industrialised Building System (IBS). This paper aims to highlight the critical issue statements related to window framing, illuminating the challenges architects, builders, and homeowners encounter in achieving practical and pleasing window frames. This research uses statistical methods and data-driven techniques to help identify potential design changes, address customer pain points, optimise performance, and encourage innovation in interlocked frame windows to meet changing consumer demands and industry standards. The results highlight the usefulness of interlocked frame windows, showing their ability to significantly increase occupant comfort, aesthetics, and overall building performance. This research explores the innovative features and benefits of frame windows, primarily emphasising their joint aspects. It discusses their potential applications in the construction industry and their transformative impact on functionality and design.